Strategi Peningkatan Kualitas Pembelajaran Melalui Pemanfaatan Media Pembelajaran Berbasis TIK - Mohamad Miftah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
The current era of digitalization 4.0 requires teachers to be able to present learning content that can help deliver learning materials and make it easier for students to receive material. The role of the teacher becomes the center of attention of stakeholders for the success of the quality of student learning. Mastery of ICT for teachers is the key to success in being able to integrate it into learning. This study aims to determine the use of learning media on the Central Java Smart portal, and factual studies on the use of ICT-based learning media on the Central Java Smart portal for PAUD level content as far as this research is used. The research method used in this study is a survey research design with qualitative descriptive techniques. This means that this study aims to produce data analysis through instruments including; questionnaires, interviews, documents, and observations. The results of the study indicate that the implication is that ICT service managers in the Central Java Province need to strengthen the socialization and training and mentoring of ICT for teachers on an ongoing basis. This outreach and training is necessary to ensure the integration of ICT in learning.